1999
DOI: 10.1046/j.1464-410x.1999.00917.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of bladder carcinoma using protoporphyrin IX fluorescence induced by 5‐aminolaevulinic acid

Abstract: The ALA-based fluorescence detection system significantly enhanced the diagnosis of malignant/dysplastic bladder lesions. However, determining the optimum drug exposure time requires further investigation using well-characterized instrumentation and study protocols, which would then allow comparison of the results from different groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
1
8

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(62 citation statements)
references
References 19 publications
(37 reference statements)
0
53
1
8
Order By: Relevance
“…b Sex. This section sums to 2813 rather than 2807 because the study by Koenig and colleagues 67 reported gender information for those enrolled (n = 55) rather than those analysed (n = 49).…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…b Sex. This section sums to 2813 rather than 2807 because the study by Koenig and colleagues 67 reported gender information for those enrolled (n = 55) rather than those analysed (n = 49).…”
Section: Figurementioning
confidence: 99%
“…In two 72,78 of these studies the whole patient population (n = 102) had a suspicion of bladder cancer and in three 51,58,84 the whole population had previously diagnosed bladder cancer (n = 117). The remaining eight studies 50,52,54,56,67,73,76,85 did not report this information. In total, 18 50,53,54,56,58,59,[61][62][63]67,[70][71][72][73]77,78,84,85 (67%) of 27 studies used 5-ALA as the photosensitising agent, five 57,60,65,66,81 (19%) used HAL, two 52,76 (7%) used hypericin and two 51,80 used either 5-ALA or HAL but did report the number of patients receiving each agent.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations